Effective Instructional Supervision and Quality Assurance in Business Education in Anambra Tertiary Institutions - Anike, Dorathy Ogochukwu; A. N. Umezulike (Sinergi International Journal of Education, 2025)
Given the critical role both effective supervision and quality assurance play in enhancing educational outcomes, this research addresses the gap in empirical studies exploring their interrelationship in the context of business education. The study focuses on four public tertiary institutions in Anambra State: Nnamdi Azikiwe University, Chukwuemeka Odumegwu Ojukwu University, Nwafor Orizu College of Education, and the Federal College of Education (Technical). A total of 138 business education lecturers participated in the study, with data collected using the Supervision of Instruction Scale (SI) and the Quality Assurance Scale (QAS). The study adopted a correlation research design, and data were analyzed using Pearson’s Product Moment Correlation Coefficient. The results revealed a low positive relationship (r = 0.321) between planning of supervision and quality assurance in business education programmes; however, this relationship was not statistically significant (p = 0.124, greater than the 0.05 alpha level). The findings suggest that while there is some connection between planning and quality assurance, the relationship is not strong enough to be considered significant. The study concludes that effective supervision of instruction is crucial for ensuring quality assurance in business education, and recommends ongoing professional development for educators, increased institutional support for supervision, and policy reforms to strengthen quality assurance mechanisms in tertiary institutions.